Covalent Patterning of Graphene for Controllable Functionalization from Microscale to Nanoscale: A Mini-Review - Li, Zhi; Li, Kai; Wang, Shuang; Teng, Chao (Frontiers in Chemistry, 2022)
Covalent patterning of graphene opens many application possibilities in the field of photonics, electronics, sensors, and catalysis due to order-dependent optical properties, band structure engineering, and processibility and reactivity improvement. Owing to the low reactivity of the graphene basal plane, harsh reagents (e.g., radicals) used for covalent functionalization normally result in poor spatial control, which largely compromises the intrinsic properties of graphene. Therefore, precisely spatial control on covalent patterning of graphene is of great importance. Herein, we summarize recent advances for covalent patterning of graphene from the microscale to nanoscale resolution using different techniques such as laser or electrochemical writing, template-directed growth, and tip-induced nanoshaving.